Ultrafine Co1-xS Attached to Porous Interconnected Carbon Skeleton for Sodium-Ion Batteries - Liu, Yangyang (Langmuir : the ACS journal of surfaces and colloids, 2019)
Carbon-based materials are effective carriers of metal sulfides because of their good volume stability and chemical stability, which can reduce volume expansion of materials and can also inhibit the interfacial reaction. In this study, Co1-xS incorporated into three-dimensional porous biomass carbon skeleton were synthesized by a template method. The three-dimensional porous carbon with large surface area is favorable for the electrolyte infiltration. The uniform distribution of Co1-xS nanoparticles results in a high reversible electrochemical reaction. The well-designed Co1-xS/three-dimensional porous carbon structure exhibits outstanding performance when used as an anode for sodium-ion batteries (SIBs). The results show that the transition mental sulfide/three-dimensional porous carbon structure has broad application prospects in SIBs